Evaluation of Heat Tolerant Chilli (Capsicum annuum L.) Genotypes in Western Terai of Nepal - Dahal, KC; Sharma, MD; Dhakal, DD; Shakya, SM (Journal of the Institute of Agriculture and Animal Science, 2006)
A field evaluation of thirteen chilli genotypes was conducted in ‘Randomized Complete Block Design’ with three replications to identify the most appropriate chilli genotypes at western terai of Nepal in spring summer of 2005. Ten heat resistant genotypes introduced from AVRDC, Taiwan to Nepal and three commercial cultivars of Nepal were planted at 50x30 cm spacing in paired row plot. All the management practices were carried out uniformly for all the treatments. Genotype CCA-119A was the earliest for 50% green fruit maturity. Fruit set percent varied significantly with the average of 18.81%. Fruit length, fruit diameter and ascorbic acid content also varied greatly. Ascorbic acid content (mg/100 g) ranged from 32.86 in CCA-984A to 173.7 in NS-1701. Wide variations were observed in yield potential of the genotypes ranging total fruit number per plant from 5.61 to 71 and in total fruit yield 7.97 to 95.33 q/ha. The genotype Mr. Lee No. 3 selex produced maximum marketable fresh fruit yield (90.69 q/ha) which was 234.5% higher than that of Jwala (check). Genotypes Susan’s Joy, CCA-119A and CCA-3288 had also 122.98, 49.06 and 25.48% higher marketable yield respectively than that of Jwala. Higher yield in genotypes Mr. Lee No. 3 selex and CCA-119A were found with better fruit set, better fruit size and more fruit number per plant while the genotype Susan’s Joy and CCA-3288 had higher yield mainly due to their predominantly larger fruit size. The genotypes with better fruit set and larger fruit size were more appropriate for the hot and dry condition of western terai of Nepal. Key words: Temperature, capsicum, fruit set, fruit number, pepper, yield J. Inst. Agric. Anim. Sci. 27:59-64 (2006)